Changes in disease characteristics of primary biliary cholangitis: An observational retrospective study from 1982 to 2016 - Takamura, Masaaki; Matsuda, Yasunobu; Kimura, Naruhiro; Takatsuna, Masafumi; Setsu, Toru; Tsuchiya, Atsunori; Osaki, Akihiko; Waguri, Nobuo; Yanagi, Masahiko; Takahashi, Toru; Sugitani, Soichi; Kobayashi, Yuka; et al. (Hepatology research, 2021)
Aim Disease characteristics of primary biliary cholangitis have changed recently. However, detailed studies on the subject have been limited. Therefore, we aimed to clarify disease characteristics of patients with recent primary biliary cholangitis using the cohort from Niigata University and 21 affiliated hospitals. Methods Overall, 508 patients were enrolled in this study from 1982 to 2016, divided into three cohorts according to their year of diagnosis: ≤1999, 2000–2009 and ≥2010. We compared differences in clinical characteristics, response to ursodeoxycholic acid and prognosis. Results The male‐to‐female ratio increased incrementally from 1:16.4 (≤1999) to 1:3.8 (≥2010) (P < 0.001). In women, the median age at diagnosis increased incrementally from 54.0 years (≤1999) to 60.5 years (≥2010) (P < 0.001) and serum albumin decreased gradually (P = 0.001), which might have affected the increase in the Fibrosis‐4 Index and albumin–bilirubin score. The ursodeoxycholic acid response rate according to the Barcelona criteria increased incrementally from 26.7% (≤1999) to 78.4% (≥2010) (P < 0.010), and those according to other criteria (Paris‐I, Rotterdam and Toronto) were approximately ≥80% in all cohorts. Ten‐year survival rate in the ≤1999 and 2000–2009 cohorts were 98.6% and 95.6%, respectively. These earlier cohorts were also characterized by a higher rate of asymptomatic state and mild histology (83.5% [≤1999] and 84.7% [2000–2009], and 93.6% [≤1999] and 91.1% [2000–2009]). Conclusions Patients with primary biliary cholangitis were characterized by older age at diagnosis and an increase in male to female ratio as well as higher response rates of ursodeoxycholic acid and longer survival, resulting from the early recognition of primary biliary cholangitis.